Presumed Risk Factors and Biomarkers for Severe Respiratory Syncytial Virus Disease and Related Sequelae: Protocol for an Observational Multicenter, Case-Control Study From the Respiratory Syncytial Virus Consortium in Europe (RESCEU). (14th August 2020) - Jefferies, Kimberley; Drysdale, Simon B; Robinson, Hannah; Clutterbuck, Elizabeth Ann; Blackwell, Luke; McGinley, Joseph; Lin, Gu-Lung; Galal, Ushma; Nair, Harish; Aerssens, Jeroen; Öner, Deniz; Langedijk, Annefleur; et al.
Abstract: Respiratory syncytial virus (RSV) is the leading viral pathogen associated with acute lower respiratory tract infection and hospitalization in children < 5 years of age worldwide. While there are known clinical risk factors for severe RSV infection, the majority of those hospitalized are previously healthy infants. There is consequently an unmet need to identify biomarkers that predict host response, disease severity, and sequelae. The primary objective is to identify biomarkers of severe RSV acute respiratory tract infection (ARTI) in infants. Secondary objectives include establishing biomarkers associated with respiratory sequelae following RSV infection and characterizing the viral load, RSV whole-genome sequencing, host immune response, and transcriptomic, proteomic, metabolomic and epigenetic signatures associated with RSV disease severity. Six hundred thirty infants will be recruited across 3 European countries: the Netherlands, Spain, and the United Kingdom. Participants will be recruited into 2 groups: (1) infants with confirmed RSV ARTI (includes upper and lower respiratory tract infections), 500 without and 50 with comorbidities; and (2) 80 healthy controls. At baseline, participants will have nasopharyngeal, blood, buccal, stool, and urine samples collected, plus complete a questionnaire and 14-day symptom diary. At convalescence (7 weeks ± 1 week post-ARTI), specimen collection will be repeated. Laboratory measures will be correlated with symptom severity scores to identify corresponding biomarkers of disease severity. Clinical Trials Registration: NCT03756766.